Pengaruh Tax Avoidance Dan Mekanisme Corporate Governance Pada Manajemen Laba - Maysani, Putu; Agung Suaryana, I Gusti Ngurah (E-Jurnal Akuntansi, 2019)
Earnings management is one of the actions taken by management to manipulate profits generated by the company for certain purposes. The research aims to find evidence about how the influence of tax avoidance and corporate governance mechanisms on earnings management is carried out by company managers. The study population is a manufacturing company listed on the IDX for the period 2013-2017, then the sample is determined by a probability sampling method with the results of 12 companies. The results of the study show that tax avoidance and board of directors have a positive effect on earnings management; independent commissioners, audit committees, institutional ownership, and managerial ownership have a negative influence on earnings management. Keywords : Earnings Management, Tax Avoidance, Corporate Governance.